A Comparative study between conventional method and the Bethesda system for reporting thyroid cytopathology (TBSRTC) - Verma, Nidhi; Singh, Chhaviraj; Sharma, S. P.; Rathi, Monika; Singh, Preeti (International Journal of Research in Medical Sciences, 2018)
Background: FNAC is widely used for the diagnosis of thyroid lesions. TBSRTC was introduced to streamline the reporting of thyroid aspirates. Objectives was to study the spectrum of various thyroid lesions in and around Meerut and comparison of conventional method and TBSRTC. Methods: A total of 464 patients were evaluated both by conventional system and TBSRTC. Results: As per conventional system of reporting, maximum number of cases were diagnosed as benign (87%), followed by malignant (6.4%), follicular neoplasia (2.5%), equivocal (2.1%) and inadequate (1.7%). As per TBSRTC, maximum number of cases were reported as category 2, 86.2% followed by category 6, 6%, category 1, 2.5% and cat 3,2.5%, category 4, 1.5% and category 5, 1%. Among benign category, maximum number of cases were of colloid goiter/multinodular goiter (MNG) (65%) followed by Hashimoto`s thyroiditis (15%), Grave`s disease (6%). Among the malignant category, maximum number of cases were of papillary carcinoma thyroid (PCT) (5.3%) followed by medullary carcinoma thyroid (MCT) (0.43%), non-Hodgkin`s lymphoma NHL (0.21%), metastatic carcinoma (0.21%), and anaplastic carcinoma (0.21%) of each. Conclusions: In present study it was found that there is an excellent agreement between the conventional system and TBSRTC. Results of both systems of reporting are comparable. In some cases, TBSRTC is almost equivalent to the conventional system in the pattern of reporting (viz. benign and malignant cat) while in some cases, TBSRTC is better in reporting (viz. FN and equivocal cat). The sensitivity of TBSRTC (93%) is slightly more as compared to the conventional system (90%) while its specificity (86%) slightly less as compared to conventional system (88%). Thus, as compared to the conventional system, TBSRTC may be viewed as a better screening test for thyroid lesions, though at the cost of specificity.